The Myth of Modularity in Rule-Based Systems for Reasoning with Uncertainty - Heckerman, David; Horvitz, Eric (1988)
In this paper, we examine the concept of modularity, an often cited advantage of the rule-based representation methodology. We argue that the notion of modularity consists of two distinct concepts which we call syntactic modularity and semantic modularity.